Editorial, Volume 11, Issue 2 - Kristy L Archuleta (Journal of Financial Therapy, 2020)
In this issue, we present four scholarly articles, two book reviews, and two professional profiles. The scholarly articles address a range of issues across diverse populations.
Keywords: financial therapy